Prevalence, awareness, and factors associated with electronic cigarette use among dental students in Costa Rica - Loría Palma, Sebastián (2026)
Background/Objectives: Electronic cigarette (e-cigarette or vape) use is increasing, especially among young adults. Since there is no data on e-cigarette use among dental students in Costa Rica, this observational study aimed to evaluate the awareness and use of vapes in students at the Faculty of Dentistry, University of Costa Rica, and identify factors that influence their use. Methods: A cross-sectional online questionnaire was administered to a sample of dental students, and their responses were assessed. A total of 244 students, with a mean age of 21.38 ± 3.29 years, were recruited between October 2024 and May 2025. Multivariate binary logistic regression was employed to analyze factors influencing ever use of e-cigarettes. Results: Of the participants, 99.17% were aware of e-cigarettes, and 60.66% had used them at least once in their lifetime, with 8.61% being current users. Sixth-year students were more likely than first-year students to believe that e-cigarettes contain carcinogenic substances (p<0.001). Participants that were unsure if vapes are more addictive than traditional tobacco cigarettes had lower odds of ever using them (OR=0.092, 95% CI: 0.009–0.491, p=0.004). Fourth-year dental students had higher odds of e-cigarette use compared to first-year students (AOR=3.050, 95% CI: 1.102–8.804, p=0.032). The survey showed that 23.84% of the participants learned about e-cigarettes from parents, friends, or classmates, and 19.94% learned about them from social media platforms like WhatsApp, Facebook, and Instagram. Conclusion: Most of the dental students demonstrated awareness of the health impacts of vaping. While more than half of the respondents had tried e-cigarettes, current use was low. Vaping behavior was influenced by academic level and perceptions of risk and addictiveness, with social networks and peers serving as primary information sources. These findings highlight the importance of integrating targeted educational interventions into dental curricula to strengthen awareness and promote evidence-based attitudes toward vaping.